2016
DOI: 10.1016/j.bbi.2016.03.024
|View full text |Cite|
|
Sign up to set email alerts
|

Mind-body interactions in the regulation of airway inflammation in asthma: A PET study of acute and chronic stress

Abstract: Background Psychological stress has long been recognized as a contributing factor to asthma symptom expression and disease progression. Yet, the neural mechanisms that underlie this relationship have been largely unexplored in research addressing the pathophysiology and management of asthma. Studies that have examined the mechanisms of this relationship in the periphery suggest that it is the superimposition of acute stress on top of chronic stress that is of greatest concern for airway inflammation. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 85 publications
1
49
0
Order By: Relevance
“…More recently, Rosenkranz et al () assessed FeNO levels in two samples of patients with mild allergic asthma, with high ( n = 15) and low ( n = 15) degrees of chronic stress, according to the University of California, Los Angeles (UCLA) Life Stress Interview (Hammen, ). Such patients were evaluated at baseline and after a stressful situation, delivered through the TSST.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Rosenkranz et al () assessed FeNO levels in two samples of patients with mild allergic asthma, with high ( n = 15) and low ( n = 15) degrees of chronic stress, according to the University of California, Los Angeles (UCLA) Life Stress Interview (Hammen, ). Such patients were evaluated at baseline and after a stressful situation, delivered through the TSST.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, while Ritz et al (, ) found increased levels of FeNO after the presentation of an acute stressor, the same group (Ritz et al, ) found a decrease in FeNO with more sustained stress, which was also associated with depression. One possible explanation for such outcomes is the different behaviours of asthmatic individuals depending on their prior stress level, as found by Rosenkranz et al (), who reported high FeNO levels among participants within the low‐stress cohort and low levels for those at high stress already at baseline. In addition, the individuals with low stress experienced a decrease in FeNO following stress administration, whereas participants with higher stress saw their FeNO levels increase after the same stimulation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, poor asthma control is highly associated with greater symptoms of anxiety and depression. 43 Individuals with high chronic stress exhibit a greater cortisol response to an acute stressor, as well as increases in blood and sputum eosinophils, whereas these relationships are opposite in those with low chronic stress. 43 Thus, a true psychoneuroimmunological association has been established between asthma and stress/anxiety.…”
Section: Asthmamentioning
confidence: 99%
“…43 Individuals with high chronic stress exhibit a greater cortisol response to an acute stressor, as well as increases in blood and sputum eosinophils, whereas these relationships are opposite in those with low chronic stress. 43 Thus, a true psychoneuroimmunological association has been established between asthma and stress/anxiety. While external stress can trigger or worsen chronic asthma, research has shown that intrinsic stress can have the same effect.…”
Section: Asthmamentioning
confidence: 99%